Cheap / worth - Kessler, Mo (2021)
The idea of “cheap” is fascinating in its contradictions and misdirection. Cheap food, cheap clothes, cheap resources… “cheap” as a descriptor under neoliberal capitalism is always a signifier of a lie. Whether it be in stolen wages or environmental destruction, there are always hidden costs required to be cheap. The drive for cheap connects labor to land through continuous efforts to reduce costs and increase profits. At the height of the Confederacy, the South had the second largest economy in the world and that economy was entirely built on stolen land, stolen labor, stolen lives and vast environmental destruction. Economies built on slavery and environmental degradation require enormous propaganda campaigns to maintain the concept of cheap. Even in a post-slavery South, the concept of cheap and the supporting propaganda dictate our current economy and government. This is the politics of extraction and disposability. The entire history of the colonized south is encapsulated in the politics of extraction and disposability. To assert alternative systems of value that defy these politics is a small but revolutionary act. From the studio to the streets, I have spent my life enacting these small rebellions. In my studio work I use formalism and aesthetics as tools of subversion of capitalist value systems. Knowing that each one on its own is not enough to create monumental system changes I act in faith that a seed planted, a lie unlearned, a moment of grace and belonging, all have the potential of transformation.